Produção e composição do leite de vacas alimentadas com fontes de energia associadas a um produto homeopático - Oliveira, Laíla Fionally Almeida de (2019)
The objective of this study was to estimate the production, composition and somatic cell count (SCC) of milk from cows fed energy sources in association with a homeopathic product. The experimental period lasted 76 days, where 16 Holstein x Gir crossbred cows were used in the middle third of lactation, with initial average body weight of 553 ± 85 kg, distributed in a 4x4 Latin square experimental design in a 2x2 factorial arrangement. The treatments used were: 1) 0 g homeopathic product + ground corn; 2) 50 g homeopathic product + ground corn; 3) 0 g homeopathic product + citrus pulp; and 4) 50 g homeopathic product + citrus pulp. The diets had as source of roughage corn silage and concentrate, formulated from ground corn or citrus pulp, soybean meal, protected fat, mineral mixture, urea, sodium bicarbonate and calcitic limestone. The diets were supplied as complete feed, with a roughage: concentrate ratio of 55:45, at 08:00 and 16:00 hours. After milking in the morning, the treatment cows with the inclusion of the hepatoprotective product received the recommended dose of 50 g / cow / day of the product. The animals were confined in individual covered pens with an area of 12.5 m². Dairy control was performed throughout the experimental period, by mechanical milking, twice a day, at 6h and 15h, in which only the milk production between 15th to 21st day of the collection period was considered. Milk yield was corrected to 3.5% fat. Experimental data were submitted to analysis of variance and comparison of means by Tukey test. All statistical procedures were conducted by SAS program considering difference when P <0.05. Dry matter intake (CMS), milk yield and fat corrected milk (LCG) were higher (P <0.05) in diets with corn as energy source. Citrus pulp favored higher (P <0.05) milk fat content. However, there was a decrease (P <0.05) in milk protein and casein content for treatments with inclusion of the homeopathic product. While lactose, total solids, milk urea nitrogen (NUL), feed efficiency, somatic cell count (CCS) and somatic cell score (ECS) (P> 0.05) did not differ between diets with energy sources associated with a homeopathic product. It was concluded that ground corn as a source of energy in the diet provided higher consumption of dry matter and milk production. The inclusion of homeopathic product in the diet caused lower protein and casein content in confined cows milk.